Beyond the infection: mapping the risk of cardiovascular events post-scrub typhus in a nationwide cohort study - Jih-Kai Yeh; Victor Chien-Chia Wu; Shao-Wei Chen; Chia-Ling Wu; Yu-Sheng Lin; Chun-Wen Cheng; Chih-Hsiang Chang; Michael Wu; Pao-Hsien Chu; Shang-Hung Chang; Yu-Tung Huang (Emerging Microbes and Infections)
Scrub typhus, caused by Orientia tsutsugamushi, often involves multiple organs, but its cardiovascular (CV) sequelae in survivors remain under-researched. This retrospective cohort study analyzed data from the National Health Insurance Research Database (NHIRD) spanning 2010–2015 to assess CV risks among scrub typhus survivors. Excluding those with prior CV events, we focused on outcomes such as acute myocardial infarction (AMI), heart failure hospitalization (HFH), strokes, new-onset atrial fibrillation (AF), aortic aneurysm or dissection, venous thromboembolism (VTE), and CV death. From 2,269 scrub typhus patients without previous CV events (mean age 47.8 ± 16.1; 38.0% female), and a matched control group (n = 2,264), we observed a higher incidence of HFH, new-onset AF, and total CV events in the scrub typhus cohort. Adjusted hazard ratios (aHRs) were 1.97 (95% CI: 1.13–3.42) for HFH, 2.48 (95% CI: 1.23–5.0) for new-onset AF, and 1.43 (95% CI: 1.08–1.91) for total CV events. Other outcomes did not significantly differ. Scrub typhus survivors exhibit an increased risk of CV events, particularly HFH and new-onset AF, underscoring the importance of heightened physician awareness and post-infection cardiac surveillance.